Sinonasal Tract Adenoid Cystic Carcinoma Ex-Pleomorphic Adenoma: A Clinicopathologic and Immunophenotypic Study of 9 Cases Combined with a Comprehensive Review of the Literature - Toluie, Sherwin (Springer US, 2012)
Primary sinonasal tract carcinoma ex-pleomorphic adenoma (CEPA) is very uncommon, with adenoid cystic carcinoma (ACC) CEPA exceptional. These tumors are often misclassified. This is a retrospective study. Nine cases of ACC CEPA included 7 females and 2 males, aged 39–64 years (mean, 51.1 years). Patients presented most frequently with obstructive symptoms (n = 5), epistaxis (n = 3), nerve changes or pain (n = 3), present for a mean of 25 months (men: 9.5 versus women: 29.4 months; p = 0.264). The tumors involved the nasal cavity alone (n = 5), nasopharynx (n = 2), or a combination of locations (n = 2) with a mean size of 2.9 cm (females: 3.3; males: 1.7; p = 0.064). Most patients presented at a low clinical stage (n = 7, stage I), with one patient each in stage II and IV, respectively. Histologically, the tumors showed foci of PA associated with areas of ACC. Tumors showed invasion (lymph-vascular: n = 4; perineural: n = 6; bone: n = 6). The neoplastic cells were arranged in tubules, cribriform and solid patterns, with peg-shaped cells arranged around reduplicated basement membrane and glycosaminoglycan material. Mitoses ranged from 0 to 33, with a mean of 8.7 mitoses/10 HPFs. Necrosis (n = 2) and atypical mitotic figures (n = 1) were seen infrequently. Immunohistochemical studies showed positive reactions for cytokeratin, CK5/6, p63, CK7, EMA, SMA, calponin, S100 protein and CD117, several highlighting luminal versus basal cells components. GFAP, CK20 and MSA were non-reactive. p53 and Ki-67 were reactive to a variable degree. Surgery (n = 8), accompanied by radiation therapy (n = 5) was generally employed. Five patients developed a recurrence, all of whom died with disease (mean, 8.4 years), while 4 patients are either alive (n = 2) or had died (n = 2) without evidence of disease (mean, 15.9 years). In summary, ACC CEPA probably arises from the minor mucoserous glands of the upper aerodigestive tract, usually presenting in patients in middle age with obstructive symptoms in a nasal cavity based tumor. Most patients present with low stage disease (stage I and II), although invasive growth is common. Recurrences develop in about a 55 % of patients, who experience a shorter survival (mean, 8.4 years) than patients without recurrences (mean, 15.9 years). The following parameters, when present, suggest an increased incidence of recurrence or dying with disease: bone invasion, lymph-vascular invasion, and perineural invasion.